REV7 confers radioresistance of esophagus squamous cell carcinoma by recruiting PRDX2. Issue 3 (8th February 2019) - Gu, Cheng; Luo, Judong; Lu, Xujing; Tang, Yiting; Ma, Yan; Yun, Yifei; Cao, Jianping; Cao, Juhua; Huang, Zeyu; Zhou, Xifa; Zhang, Shuyu
Abstract : Radiotherapy has been widely used for the clinical management of esophageal squamous cell carcinoma. However, radioresistance remains a serious concern that prevents the efficacy of esophageal squamous cell carcinoma (ESCC) radiotherapy. REV7, the structural subunit of eukaryotic DNA polymerase ζ, has multiple functions in bypassing DNA damage and modulating mitotic arrest in human cell lines. However, the expression and molecular function of REV7 in ESCC progression remains unclear. In this study, we first examined the expression of REV7 in clinical ESCC samples, and we found higher expression of REV7 in ESCC tissues compared to matched adjacent or normal tissues. Knockdown of REV7 resulted in decreased colony formation and increased apoptosis in irradiated Eca‐109 and TE‐1 cells coupled with decreased tumor weight in a xenograft nude mouse model postirradiation. Conversely, overexpression of REV7 resulted in radioresistance in vitro and in vivo. Moreover, silencing of REV7 induced increased reactive oxygen species levels postirradiation. Proteomic analysis of REV7‐interacting proteins revealed that REV7 interacted with peroxiredoxin 2 (PRDX2), a well‐known antioxidant protein. Existence of REV7‐PRDX2 complex and its augmentation postirradiation were further validated by immunoprecipitation and immunofluorescence assays. REV7 knockdown significantly disrupted the presence of nuclear PRDX2 postirradiation, which resulted in oxidative stress. REV7‐PRDX2 complex also assembled onto DNA double‐strand breaks, whereas REV7 knockdown evidently increased double‐strand breaks that were unmerged by PRDX2. Taken together, the present study sheds light on REV7‐modulated radiosensitivity through interacting with PRDX2, which provides a novel target for ESCC radiotherapy. Abstract : We confirmed that REV7 confers radioresistance in ESCC cells and tumor xenograft models. REV7‐PRDX2 binding functions pronouncedly in radioresistance of ESCC, bridging DNA repair and the anti–oxidation process.